Read all about it; Book 2 - Lori B Howard (Oxford Univ. Press, 2000)
Each of the twelve thematic units in this book contains two high-interst readings based on authentic materials, including news stories, magazine articles, biographies, folktales, and poetry. The readings and activities in each unit focus on one topic such as housing, food, or clothing; and the readers develop reading skills, vocabulary, and critical thinking through a wide variety of pre-reading, reading, and post-reading activities.